VCO (Virgin Coconut Oil) PEJATI DARI LIMBAH BUAH KELAPA PERSEMBAHAN BANTEN MANTAPKAN EKONOMI TUKANG SAPU DI AREAL PURA PENATARAN DALEM PED, NUSA PENIDA - Pradnyana, I Ketut Andika (Universitas Pendidikan Ganesha, 2021)
Penataran Dalem Ped temple is one of the heavenly temples in Nusa Penida. Based on the results of an interview with one of the sweepers in this temple, the number of pemedek (visitors who make prayers) on normal days reaches 100 people per day, Saturdays and Sundays can reach 800 people, and on certain days such as full moon and temple temple reaches 5,000 more visitors so as to produce a lot of coconut waste. Therefore it requires socialization to the community on how to process coconut into VCO. The purpose of this activity is to increase the support of partners namely sweepers at Penataran Temple Dalem Ped. The method used is counseling and practice processing coconut-based product diversification. The results obtained are partners who can produce VCO independently, partners who have knowledge of coconut processing that can be used to make VCO. After this service was carried out, the partners began to realize the importance of agricultural products to increase revenue and market their products in Nusa Penida as a typical souvenir product